The black book - Patterson, James, 1947-; Ellis, David, 1967- (2017)
Being a cop runs in Billy Harney's family. The son of Chicago's Chief of Detectives whose twin sister, Patty, also followed in their father's footsteps, there's nothing Billy won't give up for the job, including his life. Left for dead alongside his tempestuous former partner and a hard-charging assistant district attorney out for blood, Billy miraculously survives. But he remembers nothing about the events leading up to the shootout. Charged with double murder and desperate to clear his name, Billy retraces his steps to get to the bottom of what happened. When he discovers the existence of a little black book that everyone who's anyone in Chicago will stop at nothing to get their hands on, Billy suspects it contains the truth that will either set him free ... or confirm his worst fears.
Includes excerpt from the upcoming 16th seduction.
Keywords: Police -- Family relationships -- Fiction; Amnesiacs -- Fiction; Police murders -- Fiction; Murder -- Investigation -- Fiction; Elite (Social sciences) -- Corrupt practices -- Fiction; Brothels -- Fiction; suspense fiction; Police -- Illinois -- Chicago -- Fiction; Chicago (Ill.) -- Fiction; Fiction; Suspense fiction